Аксіоми успіху (нарис з життя О.В. Погорєлова) - Чирок, Я.В. (Питання історії науки і техніки, 2008)
Данная статья посвящена фигуре выдающегося ученого академика А.В. Погорелова. Автор исследует путь становления известного математика как ученого и личности, стремится оценить значение и влияние его творческого наследия на развитие украинской геометрической мысли. The given article is devoted to the figure of prominent scientist and academician О.V. Pogorelov. An author explores the way of becoming the famous mathematician as the scientist and the personality, tries to estimate the value and influencing of his creative inheritance on development of the Ukrainian geometrical idea.